Kepemimpinan Kepala Sekolah Menengah Muhammadiyah yang Progresif Bima Sakti di Era 4.0 - Mazwar Ismiyanto; Eko Prasetyo; Harun Joko Prayitno; Bambang Soemardjoko; Sabar Narimo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The research aims to describe the progressive leadership of the Muhammadiyah high school heads so that they can dig potential and inspire change for the better. Progressive leadership in the context of education in the 4.0 era reflects an active effort to exploit the potential of schools and inspire change that supports the development of pupils and the learning environment in its entirety. These indicators include the use of technology, curriculum innovation and learning methods, teacher and student competence development, partnerships with institutions, empowerment of teachers and employees. The methods used in this research are qualitative, with literature/references and interviews with the head of the Muhammadiyah High School, then analyzed and presented descriptively. The result of the research is that the Muhammadiyah High School, as an educational institution, is claimed to have the leadership to be demonstrated to effectively uncover the potential and influence of transformation. One of the basic principles of sound leadership that is applied is known as progressive leadership. This form of leadership is dedicated to the eternal evolution and rejuvenation of adaptive leadership strategies, and preserves aspirations for the days to come. The findings of this research are attitudes or characteristics of the progressive leadership of the high school of Muhammadiyah which is abbreviated by the name BIMA SAKTI (Berkemajuan, Inovatif, Moderat, Adaptif - Simpati, Amanah, Kolaboratif, Transformatif, Ijtihadi).